Perkembangan Tasawuf di Indonesia: Kajian Literatur tentang Sejarah, Tokoh, dan Peran Sufi dari Masa Klasik hingga Modern - Halimah Soewandi Putri; Dinda Putri Somantri; Achmad Junaedi Sitika (Jurnal Spiritual Healing, 2026)
Islamization in the Nusantara since the thirteenth century, which occurred through trade, politics, education, and cultural acculturation. This study aims to analyze the role of religious scholars and Sufi figures in shaping the tradition of Sufism in Indonesia, as well as its relevance in responding to the challenges of modern society. The research employs a qualitative descriptive approach based on library research, examining relevant historical sources, books, and scholarly journals. The findings indicate that Sufism played a significant role in the success of Islamization, as Sufi figures adopted strategic, contextual, ethical, and culturally accommodative approaches to preach. This is reflected in the thought and practices of figures such as Hamzah Fansuri, Syamsuddin of Sumatra, Nuruddin ar-Raniri, Abdurrauf of Singkel, Shaykh Nawawi al-Bantani, and Hamka. Subsequently, Sufism in Indonesia developed as an adaptive and moderate spiritual tradition and remains relevant as a foundation for mental, character, moral, and spiritual formation within society, particularly in confronting material crises, capitalism, and modernity.